1963
DOI: 10.1111/j.1365-246x.1963.tb05552.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetism of some Indian Rocks

Abstract: Hitherto, no palaeomagnetic data for India are available earlier than the Jurassic, 130 M.y. The remanent magnetic directions of oriented samples from one Jurassic and four pre-Cambrian rock formations in India have now been determined. One pre-Cambrian formation gave very scattered direction : the other four formations gave well-defined directions and their magnetic stability was demonstrated by a.c. and thermal demagnetization. The three pre-Cambrian results enable values of the ancient latitude and orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The latter result shows a declination, corresponding to the harder component but with a lower dip (D=79.5", 1=+8", Table I). This direction coincides with results from a reconnaissance study on rocks from the same Trap (Athavale et al, 1963; 0=70", 1=+3", 8 samples), which were obtained from thermal studies and A.F.-treatment up to 200 Oe peak value only. Our preference for the former result is based on the higher coercivity of this ma~etization component and the better grouped directions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The latter result shows a declination, corresponding to the harder component but with a lower dip (D=79.5", 1=+8", Table I). This direction coincides with results from a reconnaissance study on rocks from the same Trap (Athavale et al, 1963; 0=70", 1=+3", 8 samples), which were obtained from thermal studies and A.F.-treatment up to 200 Oe peak value only. Our preference for the former result is based on the higher coercivity of this ma~etization component and the better grouped directions.…”
Section: Discussionsupporting
confidence: 89%
“…McElhinny, 1969); 3 = Cuddapah shales and sandstones (Athavale et al,, 1970);4 = Kaimur Sandstones (McElhinny, 1968); 5 = Malani Rhyolites (Athavale et al, 1963); 6 = Upper Bhander Sandstones (Klootwijk, 1973a);7 = Purple Sandstones (McElhinny, 1969b);8 = Salt Pseudomorph Beds (Wensink, 1972). a = Hyderabad dyke (Verma et al, 1968); b = Banded hematite jasper and quartzite (Athavale et al, 1970); c = Chlitoor dyke (Athavale et al, 1970); d = Mundwara complex (Athavale et al, 1963); e = Veldurti Hematite (Verma et al, 1966). 5 The hematite deposits are younger than the base of the Cuddapah System -1400 m.y.…”
Section: Discussiommentioning
confidence: 99%
“…Paleomagnetic studies on the Upper Cretaceous to Lower Eocene plateau basalts of the Deccan traps (DEuTSCH et al, 1959) as well as on the Jurassic Rajmahal traps (CLEGG et al, 1958) and Sylhet traps (ATHAVALE et al, 1963) have demonstrated that during the Upper Mesozoic India was situated south of the equator.…”
Section: Introductionmentioning
confidence: 99%
“…513 in Klootwijk, 1974b) from 645 m.y. at the time of the extrusion of the Malani rhyofites (Athavale et al, 1963) to the Lower Cambrian.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%